2013
DOI: 10.3390/en6062759
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a Marine Microalga for Biofuel Production with Astaxanthin as a Co-Product

Abstract: Microalgae have been considered as a promising biomass for biofuel production, but freshwater resource consumption during the scaled-up cultivation are still a challenge. Obtaining robust marine strains capable of producing triacylglycerols and high value-added metabolites are critical for overcoming the limitations of water resources and economical feasibility. In this study, a marine microalga with lipid and astaxanthin accumulation capability was isolated from Bohai Bay, China. The alga was named as Coelast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 36 publications
0
12
1
Order By: Relevance
“…The results (Figure S1) showed that the growth, albeit being unsurprisingly suppressed, could still reach OD 730 at around 1.0. Compared to other studies [44], this level of cell mass was at an acceptable level. Prior to the induction condition, the algal colonies on the BG11 agar exhibited a dull-shiny texture, olive green color, and circular shape.…”
Section: Resultscontrasting
confidence: 51%
See 2 more Smart Citations
“…The results (Figure S1) showed that the growth, albeit being unsurprisingly suppressed, could still reach OD 730 at around 1.0. Compared to other studies [44], this level of cell mass was at an acceptable level. Prior to the induction condition, the algal colonies on the BG11 agar exhibited a dull-shiny texture, olive green color, and circular shape.…”
Section: Resultscontrasting
confidence: 51%
“…Coelastrum sp. HA-1, an isolated microalga from Bohai Bay, China, was cultivated under nitrogen-limiting conditions and it produced astaxanthin at a level of 6.36 mg/g dried cell weight [44]. The cultivation of Coelastrum cf.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The carbohydrate in algal biomass was quantitatively analyzed according to the NREL Laboratory Analytical Procedures [ 28 ] for biomass using a two-step acid method [ 24 ]. Approximately 1 g (dry basis) of the samples was dispensed into 200 mL Erlenmeyer flasks.…”
Section: Methodsmentioning
confidence: 99%
“…The overall crystallinity of the macroalgae subjected to the new pretreatment was examined through XRD on a Bruker D8 Advance Diffractometer with Cu Kα radiation ( λ = 0.1541 nm) at 30 kV and 30 mA [ 24 ]. The samples were scanned, and the intensity was recorded in the 2 θ range of 10°–80°.…”
Section: Methodsmentioning
confidence: 99%